2017
DOI: 10.3389/fpsyg.2017.02197
|View full text |Cite
|
Sign up to set email alerts
|

Mood As Cumulative Expectation Mismatch: A Test of Theory Based on Data from Non-verbal Cognitive Bias Tests

Abstract: Affective states are known to influence behavior and cognitive processes. To assess mood (moderately long-term affective states), the cognitive judgment bias test was developed and has been widely used in various animal species. However, little is known about how mood changes, how mood can be experimentally manipulated, and how mood then feeds back into cognitive judgment. A recent theory argues that mood reflects the cumulative impact of differences between obtained outcomes and expectations. Here expectation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 98 publications
(157 reference statements)
1
25
0
Order By: Relevance
“…Additional factors that may have influenced performance on the touch-screen task include mismatching effects (e.g., touch a negative stimulus to gain a positive reward, which has been shown to exacerbate the impact of transient emotion states on task performance (Raoult et al, 2017), and influence of attentional processes (Bar-Haim et al, 2007). For example, Aylward et al (2017) found faster responses by human participants taking part in a computer task to fearful faces compared to happy faces, which was independent of affective state (threat of electric shock).…”
Section: Discussionmentioning
confidence: 99%
“…Additional factors that may have influenced performance on the touch-screen task include mismatching effects (e.g., touch a negative stimulus to gain a positive reward, which has been shown to exacerbate the impact of transient emotion states on task performance (Raoult et al, 2017), and influence of attentional processes (Bar-Haim et al, 2007). For example, Aylward et al (2017) found faster responses by human participants taking part in a computer task to fearful faces compared to happy faces, which was independent of affective state (threat of electric shock).…”
Section: Discussionmentioning
confidence: 99%
“…Eldar et al ( 159 ) proposed the theory that mood is the cumulative result of differences in expectations and the obtained outcomes of recent experiences. Raoult et al ( 151 ) did not find strong evidence for this theory in their review of 95 papers on cognitive bias and manipulations used to affect mood. However, further research is required with more precise and overt tests of the predictions from this theory, as the studies reviewed did not have the original aim of testing Eldar's theory.…”
Section: Factors Contributing To Individual Variation In Cognitive Pementioning
confidence: 97%
“…Emotions are short-lived mental states that arise in response to rewarding or punishing stimuli ( 150 ). Emotions change rapidly and contribute to within individual variability in test performance ( 151 ). Moods, on the other hand, are longer-term mental states that are not tied to a specific stimulus and are thought to be the result of the accumulation of affective experiences in the mid- to longer-term past ( 152 , 153 ).…”
Section: Factors Contributing To Individual Variation In Cognitive Pementioning
confidence: 99%
“…To link judgement bias to welfare, the most common approach is for investigators to expose subjects to an emotion-inducing condition, such as barren versus enriched housing, using a within- or between-subjects design [ 13 , 21 ]. A more recent but less common approach is based on the assertion that individual differences in personality and mood might significantly affect cognitive bias [ 12 , 38 , 39 ]: instead of inducing a purported “good” or “poor” welfare situation on subjects, their cognitive biases have been linked to differences in personality [ 40 , 41 ], spontaneous behavior linked to affective state [ 14 , 42 , 43 ], and possibly moods induced by the tests themselves [ 44 ]. Other, less fundamental methodological variables include the nature of the reinforcement/punishment, how the subjects are conditioned to the cues, the criteria needed to pass to the testing phase, the conditions the subject faces during testing (e.g., socially isolated or not), and the total number of trials (see [ 13 ] (pp.…”
Section: Measuring Cognitive Biasmentioning
confidence: 99%